Review of Urate-Lowering Therapeutics: From the Past to the Future - Jenkins, Christopher; Hwang, Jennifer H.; Kopp, Jeffrey B.; Winkler, Cheryl A.; Cho, Sung Kweon (Frontiers in Pharmacology, 2022)
We reviewed all currently available ULT, as well as any medications in development using following databases: United States Food and Drug Administration (FDA), European Medicines Agency (EMA), Japanese Pharmaceutical and Medical Devices Agency (PMDA), and ClinicalTrials.gov. We identified a total of 36 drugs, including 10 approved drugs, 17 in clinical testing phases, and 9 in preclinical developmental phases. The 26 drugs currently undergoing testing and development include 5 xanthine oxidase inhibitors, 14 uricosurics, 6 recombinant uricases, and one with multiple urate-lowering mechanisms of action. Herein, we reviewed the benefit and risk of each drug summarizing currently available drugs. New trials of uricosuric agents are underway to develop the new indication. New drugs are going on to improve the potency of recombinant uricase and to develop the new route administration of such as oral formulation. This review will provide valuable information on the properties, indications, and limitations of ULTs.